PERITONSILLAR CELLULITIS AND QUINSY, CLINICAL PRESENTATION AND MANAGEMENT: Peritonsillar Cellulitis - Iqbal, Syed Mosaddaque; Hussain, Altaf; Mughal, Shoaib; Khan, Intesar Zahid; Khan, Ishtiaq Ahmed (Pakistan Armed Forces Medical Journal, 2009)
Objective: The study was done to find the various clinical presentations and compare the out come / prognosis of peritonsillar cellulites and guising. Study Design: A Descriptive study. Place & Duration of Study: Department of ENT and Head & Neck surgery Jinnah Medical & Dental College and Fatima Hospital, Baqai Medical University Karachi, from May 2001 to June 2006. Patients & Methods: This is a retrospective study of the treatment and their out come of 102 patients, 73 (71.6%) had peritonsillar abscess or quinsy while 29 (28.4%) had peritonsillar cellulitis who were treated indoor over a period of five years. Results: The main modality of treatment was incision & drainage of pus in 73 (71.6%) patients and needle aspiration in 29 (28.4 %) cases which resulted with 3 positive 26 negative and 5 false negative aspirates. Antibiotics given in combinations with an average stay of 5 to 8 days in the ward. Within 2 to 5 months 12 (11.7 %) cases had recurrence, while none had bilateral quinsy. Tonsillectomy was done in 35 (34.3 %) patients after 6 weeks. Conclusions: In peritonsillar infections needle aspiration is useful to differentiate between the two entities. Cellulitis usually resolves by intravenous antibiotics, when an abscess is suspected incision and drainage remains the gold standard treatment which is followed by antibiotics and tonsillectomy in selected cases.